Knowledge, attitudes and practices among people with chronic hepatitis B attending a hepatology clinic in Malaysia: A cross sectional study - Mohamed Rosmawati; Ng Chirk; Tong Wen; Abidin Suraya; Wong Li; Low Wah (BMC, 2012)
Abstract Background Hepatitis B (HBV) is the leading cause of cirrhosis and hepatocellular carcinoma worldwide. This study assessed the knowledge, attitudes and practices of people with chronic HBV and the associated factors. Methods This cross-sectional study was conducted at an outpatient adult hepatology clinic at a tertiary hospital in Kuala Lumpur. A self-administered questionnaire was administered on a one-to-one basis to assess knowledge, attitudes, and lifestyle practices of people with chronic HBV. Results The response rate was 89% (n = 483/543). Participants had a mean age of 46.3 (±14.7) years and the mean duration of HBV from time of diagnosis was 12.2 (±8.8) years. The mean knowledge score was 12.57/20 (standard deviation: ±4.4, range: 0-19). Participants aged 30-39 years, with higher educational attainment, employed in professional jobs, longer duration of diagnosis and those without cirrhosis had significantly higher knowledge scores. Age, education level and duration of diagnosis were significant predictors of the knowledge score on standard multiple regression analysis. More than half of the participants were worried of spreading HBV infection to family and friends and worried since the diagnosis. A third of the participants (33.5%) were embarrassed to reveal their diagnosis to the public but most of them (93.6%) would inform their family. Those who reported feeling worried since their diagnosis were more likely to be middle-aged, of Malay ethnicity, have shorter duration of diagnosis of less than 10 years and have received therapy. About half of the participants (50.6%) did not share dining utensils and the majority (93.2%) believed that HBV can be transmitted by sharing of eating and drinking utensils. Older patients were significantly less likely to share utensils. Those who felt worried since diagnosis had significant higher knowledge of HBV. Conclusion The findings highlight the stigma and misconceptions that still exist among the HBV patients. More patient and public education about HBV and its prevention are essential to increase awareness and to demystify the disease.